Stress and Vascular Responses: Anti-inflammatory Therapeutic Strategy Against Atherosclerosis and Restenosis After Coronary Intervention - Shiro Kitamoto; Kensuke Egashira; Akira Takeshita (Elsevier, 2003)
Atherosclerosis and restenosis after percutaneous coronary interventions have become major issues in public health in Western countries. Recent studies have revealed that inflammation plays an important role in pathogenesis of cardiovascular diseases. Vascular injury may involve an inflammatory response, which accelerates the recruitment and activation of monocytes through monocyte chemoattractant protein-1 (MCP-1). MCP-1 expression has been shown to be increased in atherosclerotic lesions and balloon injured arteries. Recently, we have devised a new strategy for anti-MCP-1 gene therapy by transfecting mutant MCP-1 gene into skeletal muscle. This mutant MCP-1 has been shown to work as a dominant-negative inhibitor of MCP-1. We here demonstrate that this strategy limited progression of pre-existing atherosclerotic lesions and improved the lesion composition into a more stable phenotype in the hypercholesterolemic mice. This strategy also suppressed monocyte infiltration/activation in the injured site and markedly inhibited restenotic changes (neointimal hyperplasia) in the carotid artery in rabbits, rats, and monkeys after balloon injury or stent implantation. Therefore, MCP-1-mediated monocyte infiltration is essential in the development of restenotic changes as well as atherosclerosis progression. MCP-1 can be a practical therapeutic target for human restenosis and atherosclerosis.